EMPOWERING CARE’S EFFECTIVENESS FROM HIGH SCHOOL MATH TO COLLEGE ENGLISH - Walker, Deron (LLT Journal: A Journal on Language and Language Teaching, 2020)
***In this paper, Sunnyside High School, Inland Empire University (IEU) and Desert Valley, California will serve as pseudonyms to maintain the anonymity of the high school, university, district and city.  Ms. Jasmine Espinoza and Dr. J. D. Hyde will represent the pseudonyms for the teacher-participants who taught the classes examined in this study.  Abstract:Building upon the prior success of a rookie high school math teacher, a veteran English professor also successfully implemented empowering care at a private university in that same urban setting in Southern California.  The aforementioned empowering care that contributed to better student learning as measured by district wide tests at the high school level now demonstrated pedagogical success as assessed by student evaluations in the university setting.   The purpose of this paper, chronicled from a practitioner?s point of view, examines how teacher beliefs that ?all students are capable of learning,? operationalized concretely in terms of empowering care, enabled students to achieve impressive academic performances on the aforementioned measures in their respective settings over two consecutive school years (D. Walker & S. Walker, 2019).